Pengembangan Media Komik Etnomatematika pada Alat Musik Sasak untuk Meningkatkan Hasil Belajar Siswa di SMPN 1 Lingsar - Azzahra, Sakinah; Turmuzi, Muhammad; Tyaningsih, Ratna Yulis (Pendidikan Matematika FKIP Universitas Mataram, 2025)
The abstract nature of mathematics often makes students feel challenged, bored, and even anxious during the learning process. Therefore, mathematics learning should be interactive, enjoyable, and motivating. This study aimed to develop ethnomathematics-based comic learning media that connects the concept of cylindrical solid geometry with the traditional Sasak musical instrument Gendang Beleq to improve the mathematics learning outcomes of 29 seventh-grade students at SMPN 1 Lingsar, consisting of 10 male and 19 female students. The research employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate), but was limited to the Develop stage. Research instruments included validation sheets, practicality questionnaires, and learning achievement tests. The analysis focused on the validity, practicality, and effectiveness of the media. The results indicated that the developed comic media was categorized as “highly valid” with an average percentage of 81.73%, “highly practical” with an average percentage of 92.65%, and “effective” with an N-Gain score of 0.73 (high category). Furthermore, this media successfully increased students’ learning interest, reinforced contextual conceptual understanding, and fostered an appreciation of local culture. The visual and narrative presentation of the comic made the learning process more enjoyable and meaningful.